It’s All About Emotions : Narratives of highly skilled migrants: A study of Swiss in Israel and Israelis in Switzerland - Oberlé, Hélène Mona (2023)
Abstract The study focuses on highly skilled migrants, specifically, Swiss in Israel and Israelis in Switzerland. The attention of the study lies on the significance of migration within (multi-sited) biographies. Focusing on twelve main protagonist, Hélène Mona Oberlé analyses and discusses the perceptions, interpretations, and varying uses of emotions in migration-narratives.Three main themes are presented: first, feelings of (non-)belonging to places and specific groups; second, past, present and future in the form of nostalgia, irritation and expectation; third, notions of “going abroad” as a feeling of accomplishment emerging within the narratives. Overall, the protagonists construct a self which is flexibly adapted to the empirical reality of globalization, experiences struggles and tensions yet creates meaningful connections to specific places and times through the use of various emotions.Die Studie thematisiert hochqualifizierte Schweizer:innen in Israel und Israelis in der Schweiz und fragt nach der Bedeutung von Emotionen in Migrationserzählungen und (mehrfach verorteten) Biografien. Hélène Mona Oberlé analysiert und diskutiert die Wahrnehmungen, Interpretationen und unterschiedlichen Emotionen, die in den Erzählungen von zwölf ausgewählten Protagonist:innen aufkommen. Dabei geht es insbesondere um drei Hauptthemen: Gefühle der (nicht-)Zugehörigkeit zu Orten und Gruppen; Narrative von Vergangenheit, Gegenwart und Zukunft in Verbindung mit Gefühlen von Nostalgie, Irritation und Erwartung; das „ins Ausland gehen“ als Erfolgsgefühl. Die Protagonist:innen konstruieren mit ihren Erzählungen ein flexibles Selbst, das sich an die Herausforderungen und Spannungen einer globalisierten Welt anpasst und gleichzeitig durch Emotionen bedeutsame Verbindungen zu Orten und Zeitpunkten erschafft.